Chosen induvidual factors of adolescents' physical development in their leisure time - Karol Görner; Adam Jurczak; Robert Makuch; Dariusz Mucha; Michał Spieszny (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2013)
The aim of the research was to diagnose chosen individual factors of adolescents’ physical development (motor skills, physical fitness, motor activity needs) and their influence on their actual level of physical activity in their leisure time. The subjects of the research were students of Cracow’s junior high schools. The probability sample of 295 girls and 329 boys were examined. The method used was a survey. The results of the examinations showed that the chosen individual factors had an influence on the actual level of physical activity in their leisure time. The boys’ motor skills (in contrast with the rest of the factors) correlated the least with the increase of the actual level of physical activity in leisure time, and in case of the girls, they did not correlate at all. Youngsters’ individual predispositions to undertake physical activity in their free time were at a medium-high level. Nevertheless, their internalization did not take place because more than a half of the subjects undertook physical activities at a low level (51.0%) or not at all (7.4%).